IMPLEMENTASI SENSOR KELEMBAPAN DAN PH TANAH UNTUK OPTIMALISASI PERTUMBUMBUHAN TANAMAN SELEDRI - Dedy Harto; Kharis Hudaiby Hanif; Farhan Muhammad Nabil (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
Soil moisture and pH are important factors that influence the growth of celery (Apium graveolens). Manual monitoring of soil conditions is often ineffective because it cannot provide real-time soil condition information. This study aims to implement a sensor-based soil moisture and pH monitoring system to support the optimization of celery plant growth. The developed system uses a YL-96 soil moisture sensor and a soil pH sensor integrated with a microcontroller to measure and monitor soil conditions. Based on testing of 10 field data samples, the system is able to identify the